UJI AKTIVITAS TABIR SURYA EKSTRAK DAN LOTION KUNYIT (Curcuma domestica Val.) SECARA INVITRO MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Alfian, Muhammad; Hasanudin, Muhammad Nurul; Maulana, Mochamad Luqni; Mustainin, Muhammad (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Excessive UV B radiation can lead to premature skin aging, but research suggests that turmeric (Curcuma domestica Val.) may have antioxidant compounds that could serve as a sunscreen. To investigate, the researchers tested turmeric extracts and lotions in vitro using a UV-Vis spectrophotometer. They extracted turmeric by maceration with 70% ethanol to obtain a thick extract, then evaluated the physical characteristics of turmeric lotion preparations including organoleptics, spreadability, adhesion, pH, SPF values (using the Mansur method), and Erythema Transmission Percentage (%T) in vitro using a UV-Vis spectrophotometer with absorbance wavelengths of 290-320 nm. The results showed that F1 to F5 turmeric lotion preparations were semi-solid, brownish yellow, fragrant, with spreadability above 7 cm, adhesion less than 1 second, and pH below 8. The highest SPF value of turmeric extract was at a concentration of 500 mg with SPF 46, while the highest SPF of turmeric lotion was F5 with SPF 15. All turmeric extracts are categorized as sunblock, while F5 lotion is also sunblock and F1 to F4 lotions are fast-tanning. Although the SPF value decreases when turmeric extract is made into a lotion, it still has sunscreen potential.